2010
DOI: 10.1182/blood-2009-11-251199
|View full text |Cite
|
Sign up to set email alerts
|

Neogenin inhibits HJV secretion and regulates BMP-induced hepcidin expression and iron homeostasis

Abstract: Neogenin, a deleted in colorectal cancer (DCC) family member, has been identified as a receptor for the neuronal axon guidance cues netrins and repulsive guidance molecules repulsive guidance molecules (RGM). RGMc, also called hemojuvelin (HJV), is essential for iron homeostasis. Here we provide evidence that neogenin plays a critical role in iron homeostasis by regulation of HJV secretion and bone morphogenetic protein (BMP) signaling.Livers of neogenin mutant mice exhibit iron overload, low levels of hepcidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
106
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(112 citation statements)
references
References 47 publications
3
106
0
3
Order By: Relevance
“…Neogenin mutant mice (neogenin m/m ), kindly provided by Dr. Sue Ackerman (The Jackson Laboratory), were maintained in C57BL/6 strain background as described previously (Mitchell et al, 2001;Lee et al, 2010;. Neogenin f/f (neo f/f ) mice were generated by Ozgene as illustrated in Figure 6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neogenin mutant mice (neogenin m/m ), kindly provided by Dr. Sue Ackerman (The Jackson Laboratory), were maintained in C57BL/6 strain background as described previously (Mitchell et al, 2001;Lee et al, 2010;. Neogenin f/f (neo f/f ) mice were generated by Ozgene as illustrated in Figure 6.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, neogenin is important for endochondral bone formation , neural tube formation (Mawdsley et al, 2004;Kee et al, 2008), digit patterning (Hong et al, 2012), ion metabolism (Zhang et al, 2005;Kuns-Hashimoto et al, 2008;Lee et al, 2010), and muscle differentiation (Kang et al, 2004). Neogenin is highly expressed in the embryonic and adult neural stem cells (NSCs) (Gad et al, 1997;Fitzgerald et al, 2007;van den Heuvel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There were no hematologic abnormalities suggestive of the presence of a secondary, anemia-induced iron overload phenotype in mice with liverspecific Alk2 or Alk3 deficiency (supplemental Figure 3). Moreover, hepatic expression of hereditary hemochromatosis diseasecausing genes, including transferrin receptor-2 (Tfr2), 30 Hfe, 31,32 hemojuvelin (Hjv), 9,13,14,33 and ferroportin 1 (Fpn1), 34 did not differ between genotypes (supplemental Figure 4). These results demonstrate a mild iron overload phenotype in Alk2 fl/fl ; Alb-Cre mice and a severe iron overload phenotype in Alk3 fl/fl ; Alb-Cre mice and indicate that both Alk2 and Alk3 have roles in the regulation of systemic iron homeostasis.…”
mentioning
confidence: 99%
“…5,6 Recent studies have demonstrated a critical role for bone morphogenetic protein (BMP) signaling in the regulation of hepcidin expression by iron. [7][8][9][10][11] Binding of BMP ligands to type I and type II BMP receptors induces the type II receptor to phosphorylate and activate the type I receptor. The activated type I receptor, in turn, phosphorylates intracellular signaling molecules, including SMADs 1, 5, and 8.…”
Section: Introductionmentioning
confidence: 99%
“…The most compelling evidence is the iron overload observed in the livers of mice in which the gene encoding Neogenin (NEO) has been knocked out [28]. Structural experiments showing a direct physical interaction with RGMs acting as a link between these two signaling pathways led to the crystal structure of a ternary complex comprising the BMP ligand BMP2, the full-length extracellular domain of RGMb, and the two membrane proximal FNIII domains of Neogenin [17].…”
Section: Structural Insight Into Ligand-receptor Interactionsmentioning
confidence: 99%